Effects of cichorium intybus on GABA(A) receptors and apoptosis in pentylenetetrazole-induced kindling in rats - Ergül Erkeç, Özlem; Meral, İsmail; Kara, Mehmet; Eşrefoğlu, Mukaddes; Tok, Olgu Enis; Üstünova, Savaş; Armağan, Metin (Kare Publishing, 2021)
Objectives: This study was designed to determine the effects of Cichorium intybus (CI) on apoptosis and GABA(A) receptor density in the brains of rats in pentyleneterazole induced kindling. Methods: The rats were divided into three groups: Control group, pentylenetetrazol administered (PTZ) group, and PTZ+CI extract administered (PTZ+CI) group. Control group received only physiological saline (0.5 ml). PTZ (35 mg/kg) injected to the animals in the PTZ and PTZ+CI groups. The CI extract (200 mg/kg) was also administered to the PTZ+CI group. A 75 mg/kg challenge dose of PTZ was administrated to the PTZ treated groups, on the 12th injection. Results: A significant increase was found in the number of neurons expressing the GABA(A) receptor in the brain tissue (hippocampus and cerebral cortex) of the PTZ group when compared to the control. The density of GABA(A) receptor of the neurons in the cerebral cortex significantly increased in PTZ administered groups compared to the control.The number of apoptotic neurons was found non-significant between groups in the brain. Conclusion: CI treatment prolonged the onset of the first seizure activity and seizure latency at a convulsive dose, and kept the number of GABA(A) receptors close to that of the control in the hippocampus.

Amaç: Bu çalışma, pentileterazole indüklü kindlingte, Cichorium intybus’un sıçanların beyinlerinde apoptoz ve GABAA reseptör yoğunluğu üzerindeki etkilerini belirlemek için tasarlanmıştır. Gereç ve Yöntem: Sıçanlar üç gruba ayrıldı: Kontrol grubu, pentilentetrazol uygulanan (PTZ) grup ve PTZ + Cichorium intybus ekstresi (PTZ + CI) uygulanan grup. Kontrol grubu sadece serum fizyolojik (0.5 ml) aldı. PTZ ve PTZ + CI gruplarındaki hayvanlara PTZ (35 mg/kg) enjekte edildi. PTZ + CI grubuna ayrıca CI ekstraktı da (200 mg/kg) uygulandı. PTZ uygulanan gruplara 12. enjeksiyonda 75 mg/kg’lık bir PTZ dozu uygulandı. Bulgular: PTZ grubunun beyin dokusunda (hipokampus ve tüm beyin) GABAA reseptörünü ifade eden nöronların sayısında kontrole göre önemli bir artış bulundu. Tüm beyindeki nöronların GABAA reseptör yoğunluğu, kontrol grubuna kıyasla PTZ uygulanan gruplarda önemli ölçüde artmıştır. Beyindeki apoptotik nöronların sayısı gruplar arasında anlamsız bulundu. Sonuç: Sonuç olarak, Cichorium intybus uygulması, konvülsif dozda ilk nöbet aktivitesi oluşumu ve nöbet latansını geciktirdi ve hipokampusta GABAA reseptörlerinin sayısını kontrole yakın tuttu.
Sıçanlarda Pentilentetrazol Kindlingde Cichorium Intybus’un GABAA reseptörleri ve apoptoz üzerine etkileri
Keywords: Brain; Cichorium Intybus; Epilepsy; Hippocampus; Kindling; Pentyleneterazole; Seizure; Beyin; Cichorium Intybus; Epilepsi; Hipokampus; Kindling; Nöbet; Pentileneterazol